Association of Cord Blood Bilirubin with Neonatal Hyperbilirubinemia: A Hospital Based Study - Suresh Chander Jain; Kuldeep Singh Ahlawat; Abhinay Jain (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Around 60% of term newborns have jaundice within the first week of life. Increased bilirubin synthesis (due to red blood cell breakdown), incorrect uptake, and decreased clearance by the young liver induce this physiological change. Jaundice is a typical condition among infants. Neonatal hyperbilirubinemia (NH) can induce kernicterus in otherwise healthy newborns. Subjects and Methods: After meeting the eligibility criteria, a minimum of 74 healthy full-term babies were enrolled. All full term neonates (Gestation age 37 weeks to 42 weeks) are included in our study, regardless of mode of delivery, and newborns with risk factors for severe hyperbilirubinemia, such as jaundice observed within the first 24 hours, ABO and/or Rh incompatibility, cephalohematoma or significant bruising, significant co morbidities requiring N.I.C.U. admission, are excluded. Results: This cross-sectionall study included 74 healthy term newborns who were monitored during the first five days after birth. The findings of the investigation were analysed utilising statistical methods. Conclusion: Significant hyperbilirubinemia affects 5.4 percent of the people in our sample. TSB 15 mg/ dl at 48 hours of life is considered significant jaundice.